miRNA-seq of Echinococcus multilocularis Extracellular Vesicles and Immunomodulatory Effects of miR-4989 - Ding, Juntao; He, Guitian; Wu, Jin’en; Yang, Jing; Guo, Xiaola; Yang, Xing; Wang, Ying; Kandil, Omnia M.; Kutyrev, Ivan; Ayaz, Mazhar; Zheng, Yadong (Frontiers in Microbiology, 2019)
Alveolar echinococcosis caused by Echinococcus multilocularis is an important zoonotic disease. In the infected mice, emu-miR-4989-3p is present in sera, but its role remains unknown. Using high-throughput sequencing and qPCR, emu-miR-4989-3p was herein confirmed to be encapsulated into E. multilocularis extracellular vesicles. In the transfected macrophages, emu-miR-4989-3p was demonstrated to significantly inhibit NO production compared to the control (p < 0.05). Moreover, transfection of emu-miR-4989-3p also gave rise to the increased expression of TNF-α (p < 0.01). Furthermore, emu-miR-4989-3p induced the dysregulation of several key components in the LPS/TLR4 signaling pathway compared with the control, especially TLR4 and NF-κB that both were upregulated. Conversely, the NO production and the expression of TNF-α, TLR4 and NF-κB tended to be increased and decreased in the mimics-transfected cells upon emu-miR-4989-3p low expression, respectively. These results suggest that emu-miR-4989-3p is one of ‘virulence’ factors encapsulated into the extracellular vesicles, potentially playing a role in the pathogenesis of E. multilocularis.